A scoping review of spine surgeries between specialties: comparing neurosurgeons versus orthopedic surgeons - Trinidad, Leo E.; Orata , Rhoby U. (International Journal of Research in Medical Sciences, 2023)
Spine surgeries are both performed by neurosurgeons and orthopedic surgeons. However, there remains controversy whether surgeon specialty affects spine surgery outcomes and complications. The objective of this scoping review was to map the existing knowledge comparing the outcomes and complications of spine surgeries between neurosurgeons and orthopedic surgeons. Eligible studies are any English-written or -translated published journals written from year 2000 onwards that compared outcomes and/or complications of spine surgeries between neurosurgeons and orthopedic surgeons. Excluded papers are those which do not dichotomize or specify the surgeon specialty to either neurosurgeon or orthopedic surgeon. Medline database was used to systematically search for papers that compare the two specialties. Ten studies were selected which directly compared spine surgery outcomes of the two specialties, all of which are retrospective studies and most of it relied on the national database. Specific spine surgeries were varied between all studies. Overwhelmingly, these studies showed no significant differences between neurosurgeons and orthopedic surgeons in short term outcomes while there were some significant differences in complications. Based on this scoping study, surgeon specialty, whether neurosurgery or orthopedics, has no significant association in spine surgery outcomes. This may imply that despite the differences in training, patients may have good outcomes if treated by either specialty. However, questions remain whether the effect of further training after residency or fellowship, length of experience and number of cases of both surgeon specialties have a causal effect in outcomes of spine surgeries.